Show Me The Data: The Pilot UK Research Data Registry - Alexander Ball; Kevin Ashley; Patrick McCann; Laura Molloy; Veerle Van den Eynden (International Journal of Digital Curation, 2014)
The UK Research Data (Metadata) Registry (UKRDR) pilot project is implementing a prototype registry for the UK’s research data assets, enabling the holdings of subject-based data centres and institutional data repositories alike to be searched from a single location. The purpose of the prototype is to prove the concept of the registry, and uncover challenges that will need to be addressed if and when the registry is developed into a sustainable service. The prototype is being tested using metadata records harvested from nine UK data centres and the data repositories of nine UK universities.